2014
DOI: 10.5194/bg-11-4361-2014
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of drainage, nutrient status and management practice on the full carbon balance of grasslands on organic soils in a maritime temperate zone

Abstract: Abstract. Temperate grasslands on organic soils are diverse due to edaphic properties but also to regional management practices and this heterogeneity is reflected in the wide range of greenhouse gas (GHG) flux values reported in the literature. In Ireland, most grasslands on organic soils were drained several decades ago and are managed as extensive pastures with little or no fertilisation. This study describes a 2-year study of the net ecosystem carbon balance (NECB) of two such sites. We determined GHG flux… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 62 publications
(66 reference statements)
1
33
0
Order By: Relevance
“…Indeed respiration appreciably exceeded Gross Primary Production (GPP) at Site B, but was similar to GPP at Site A ( Fig. 5; Renou-Wilson et al 2014).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Indeed respiration appreciably exceeded Gross Primary Production (GPP) at Site B, but was similar to GPP at Site A ( Fig. 5; Renou-Wilson et al 2014).…”
Section: Discussionmentioning
confidence: 84%
“…Thus compared to DOC, fluvial CO 2 fluxes and evasion have generally accounted for smaller fractions of the net terrestrial C balances of undisturbed temperate peatland systems, however this was not the case at our sites. The component fluxes of the terrestrial C balance of the study sites given by Renou-Wilson et al (2014) are shown in Fig. 5 for comparison with the fluvial C fluxes.…”
Section: Fluvial C Fluxes As Components Of Terrestrial C Balancesmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem can be overcome by adequately pooling flux data to the respective plant phenological stages (cluster‐wise approaches). Although the improvement is small compared with the overall variability and therefore may not be significant, this result fits well with the recommendations of other studies that have suggested the use of vegetation proxies to account for plant phenological stages for improved R ECO and NEE modeling ( Burrows et al, ; Kandel et al, ; Renou‐Wilson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Wallin et al, 2010;Billett and Harvey, 2013), which could explain lower direct measurements of CO2 emissions from drainage ditches in the studies described above. Comparing two drained peatlands under grassland, Renou-Wilson et al (2014) recorded mean excess CO2 in drainage water of 4.3 g C m -2 yr -1 in a nutrient rich site, and 16 g C m -2 yr -1 in a nutrient-poor site, the latter representing around 60% of the total fluvial C flux during a dry year.…”
Section: On-site Emissions Of Other Ghgs From Drainage Channelsmentioning
confidence: 94%